Diode laser photoablation to correct distal nasolacrimal duct atresia in an adult horse. (25th March 2014) - Stoppini, Riccardo; Tassan, Stefano; Barachetti, Laura
Abstract: Case description: An 8‐year‐old Hanoverian mare was presented for chronic mucopurulent discharge in the left eye, which was responsive to topical antibiotic therapy. Clinical findings: The nasolacrimal orifice was absent in the left nasal meatum, and anterograde irrigation of left nasolacrimal duct was not possible. Dacryocystorhinography was performed and revealed about 4‐6 cm of distal nasolacrimal duct atresia. Surgical treatment and outcome: A novel technique was attempted with the horse under standing sedation using an urinary catheter and a 980 nm diode laser with a 600 μm diameter flexible bare quartz fiber. A nasolacrimal orifice was successfully created by ablating the nasal mucosa directly over the tip of the urinary catheter, and patency was maintained with a soft catheter sutured in place for 4 weeks. At 3 months re‐evaluation, the left nasolacrimal duct was patent and functional. Conclusion: This case report describes a successful novel surgical technique used to correct congenital distal nasolacrimal duct atresia in an adult horse under standing sedation. Advantages over conventional surgical techniques are shorter operating time and limited hemorrhage.